2007
DOI: 10.1038/ncb1578
|View full text |Cite
|
Sign up to set email alerts
|

Priming, initiation and synchronization of the segmentation clock by deltaD and deltaC

Abstract: Zebrafish somitogenesis is governed by a segmentation clock that generates oscillations in expression of several Notch pathway genes, including her1, her7 and deltaC. Using a combination of pharmacological inhibition and Mendelian genetics, we show that DeltaD and DeltaC, two Notch ligands, represent functionally distinct signals within the segmentation clock. Using high-resolution fluorescent in situ hybridization, the oscillations were divided into phases based on eight distinct subcellular patterns of mRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
155
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 104 publications
(162 citation statements)
references
References 35 publications
6
155
1
Order By: Relevance
“…In zebrafish, the synchronization of the segmentation clock is realized by intercellular interaction via Delta-Notch signaling (11-13, 30, 31). Previous models have confirmed that this interaction successfully leads to the synchronization of oscillation among cells (24,25,30).However, previous analyses did not answer the following questions: (i) In the actual segmentation process, dynamic rearrangement of relative cell positions due to cell proliferation and movement is observed in the PSM (12,32,33). Can the synchronization of the segmentation clock be achieved and stably sustained under such random cell movement?…”
mentioning
confidence: 74%
See 3 more Smart Citations
“…In zebrafish, the synchronization of the segmentation clock is realized by intercellular interaction via Delta-Notch signaling (11-13, 30, 31). Previous models have confirmed that this interaction successfully leads to the synchronization of oscillation among cells (24,25,30).However, previous analyses did not answer the following questions: (i) In the actual segmentation process, dynamic rearrangement of relative cell positions due to cell proliferation and movement is observed in the PSM (12,32,33). Can the synchronization of the segmentation clock be achieved and stably sustained under such random cell movement?…”
mentioning
confidence: 74%
“…However, previous analyses did not answer the following questions: (i) In the actual segmentation process, dynamic rearrangement of relative cell positions due to cell proliferation and movement is observed in the PSM (12,32,33). Can the synchronization of the segmentation clock be achieved and stably sustained under such random cell movement?…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, mutants for different Delta ligands are observed to affect oscillation patterns in the PSM in different ways, suggesting more than the single role of synchronisation in the PSM for Notch-Delta signalling [4,5], or at the very least a complex interaction between Notch-Delta signalling components and the somitogenesis clock.…”
Section: Introductionmentioning
confidence: 99%